Hubungan Usia, Lama Paparan Debu, Penggunaan APD, Kebiasaan Merokok Dengan Gangguan Fungsi Paru Tenaga Kerja Mebel Di Kec. Kalijambe Sragen - Pinugroho, Setyo Bintang; , Yuli Kusumawati, SKM., M.Kes (2017)
Impaired lung function is a sign of disease of the respiratory system that can disrupt the body's metabolism and lowers productivity. Impaired lung function often occurs in workers exposed to dust as furniture factories. This study aimed to analyze the relationship between age, duration of exposure, the use of safety protect and smoking with impaired lung function. This type of research is observational analytic with cross sectional approach. This study population all workers who work at UD. Indri Jati and UD. Wanna Jati subdistrict, Sragen Kalijambe amounted to 53 people. Samples taken as a whole (Exhaustive Sampling). Collecting data using questionnaires and measurements of lung function with spirometry capacity. Data were analyzed using statistical test Chi- Square. The results showed no relationship between age (p = 0,021) and smoking (p = 0,019) with impaired lung function, while the variable long-exposure (p = 0,740) and use of safety protect (p = 0,250) no association with impaired lung function.